Pentingnya Peran Logo Dalam Membangun Branding Pada UMKM Rajutan BKL Bismo - Aulia Afra Destrina; Galvin Christian Lukyanto; Mentari Clara Dewanti; Siti Aminah (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Branding is very important in starting a business. With the branding can increase sales and attractiveness to consumers. Branding by giving a logo that has meaning, developing social media, creating a website for SMEs in this way can be known by the public. The logo in MSMEs is also very important, the goal is for sellers to have their own brand or brand and also with the logo of the products being sold, they can be recognized by the public. In branding MSMEs, it is necessary to create content for MSMEs, create MSME social media, MSME websites and create a new logo for MSMEs, therefore MSMEs in Blitar Village can maximize sales and introduce these products.